A high-voltage, cycle-stable high-nickel cathode material and its preparation method and application
By forming a layered structure of LixAOy type lithium-ion conductor cladding and rare earth metal doped on high-nickel positive electrode material, the problem of instability of material structure at high voltage is solved, and the high voltage cycle stability and rate performance are improved , simplifies the process and reduces costs.
Patent Information
- Application Number
- CN202111282452.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-01
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-11-01
AI Technical Summary
The existing high-nickel positive electrode materials have unstable structures under high voltage conditions, resulting in rapid capacity attenuation and reduced cycle life. The existing doping and coating processes are complex and the high voltage performance is not ideal, making it difficult to achieve high voltage cycle stability.
High nickel matrix material was prepared by co-precipitation method, and LixAOy type lithium-ion conductor cladding was generated on its surface in situ. Combined with the Re doping of rare earth metal element, it formed a reinforced layered structure, and ensured element A and Re through hydrothermal treatment and calcination technology. The elements are evenly distributed to form a stable modified layer and lattice structure.
A high-nickel positive electrode material with high voltage cycling stability is realized, which enhances the layered structural stability of the material and lithium ion transmission performance, simplifies the preparation process and reduces costs, and significantly improves the rate performance and cycle stability of the material.
Smart Images

Figure CN116062802B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-nickel positive electrode material for lithium ion batteries and a preparation method and application thereof, belonging to the field of positive electrode materials for lithium ion batteries. Background Art
[0002] Lithium-ion batteries (LIBs) have become a research hotspot in the field of energy storage due to their advantages such as high capacity, high operating voltage, long cycle life and low self-discharge rate. Rechargeable LIBs were introduced to the consumer market in the early 1990s, triggering a revolutionary wave of portable electronic technology around the world. Now, LIBs also show broad application prospects in fields such as pure electric vehicles (EVs), hybrid electric vehicles (HEVs) and smart grids. However, compared with traditional internal combustion engines, the energy density of LIBs needs to be further improved. As one of the most critical components of lithium-ion batteries, the positive electrode material is the key to determining the energy density of LIBs. Therefore, the design and preparation of suitable positive electrode materials is of great importance to achieving high energy density (output capacity × output voltage) LIBs. So far, the positive electrode materials that have been applied mainly include LiCoO2, LiFePO4, LiMn2O4, LiNi 1-x-y Co x Mn y O2, among which high nickel materials (Ni content ≥ 0.5) have become the mainstream choice of next-generation positive electrode materials due to their low price, high discharge capacity and output voltage. As the voltage range widens, the energy density of high nickel positive electrode materials will be further improved, however, more rapid capacity decay and reduced cycle life will also occur. The main reasons are as follows: Under the high delithiation state caused by high voltage, the highly reactive Ni 4+ It is easy to react with organic electrolytes, causing the material to undergo an irreversible phase change and lose its electrochemical activity. In addition, repeated lithium insertion and extraction will also cause fatigue of the material's lattice structure, which will then produce cracks, exposing more particle surfaces to the electrolyte, accelerating the irreversible phase change reaction rate and causing more severe performance degradation. How to improve the structural stability of the high-nickel cathode material itself under high voltage conditions and prevent the reconstruction of the particle surface is crucial to the development of high-nickel cathode materials with high voltage cycle stability.
[0003] Existing studies have shown that bulk doping and surface coating are common methods to improve the performance of high-nickel cathode materials. For example, the literature (J.Phys.Chem.C 2016,120,3235-3241) reported the use of Ni 0.80 Co 0.15 Al 0.05 (OH)2 is used as a precursor, and after mixing with lithium hydroxide and sodium carbonate and calcining, LiNi doped with Na is obtained. 0.8 Co 0.15 Al0.05 O2 material, compared with undoped LiNi 0.8 Co 0.15 Al 0.05 Although the initial capacity of O2 materials and Na-doped high nickel materials is slightly reduced, their rate performance and cycle performance are greatly improved. 0.80 Co 0.15 Al 0.05 (OH)2 is used as a precursor, mixed with Al2O3 by spray drying, and then mixed with lithium hydroxide and calcined to obtain LiNi with LiAlO2 coating. 0.8 Co 0.15 Al 0.05 O2 secondary particles, compared with unmodified LiNi 0.8 Co 0.15 Al 0.05 The initial charge and discharge capacity, rate performance and cycle performance of the secondary particles coated with LiAlO2 and LiAlO2 have been greatly improved. Although the existing doping and coating processes can effectively improve the electrochemical properties of high-nickel positive electrode materials, the existing preparation process is relatively complicated, and the electrochemical performance of the material under high voltage is not ideal, which is not conducive to the further application of high-nickel materials. Summary of the invention
[0004] In order to overcome the deficiencies of the prior art, the present invention aims to provide a high-nickel positive electrode material for lithium-ion batteries with high voltage cycle stability, relatively simple preparation process, low cost and broad application prospects, and a preparation method thereof.
[0005] On the one hand, the present invention provides a high-voltage cycle-stable high-nickel positive electrode material, comprising a high-nickel base material and a modified layer coated on the surface of the high-nickel base material; the structural formula of the modified layer is Li x AO y ; Wherein A is selected from one or more combinations of phosphorus, silicon, boron and aluminum, and 1≤x≤3, 1≤y≤5; The general structural formula of the high nickel matrix material is LiNi z Z 1-z O2, wherein Z is at least one of cobalt, manganese, iron, and aluminum, 0.5≤z<1, and the high nickel matrix material is doped with rare earth metal elements Re, wherein Re is selected from at least one of lanthanum, cerium, praseodymium, samarium, scandium, and yttrium.
[0006] In the present invention, the high nickel cathode material is a new structural design, having an in-situ generated lithium ion conductor coating layer (i.e., a modified layer Li x AO y), which can effectively stabilize the material surface interface, prevent the deactivation side reaction with the electrolyte and thus improve the material's cycle stability. Moreover, the high-nickel positive electrode material with high voltage cycle stability has a reinforced layered structure (formed by doping the nickel matrix material with the rare earth metal element Re), which avoids the collapse and cracking of the layered lattice structure under the high lithium removal state caused by high voltage, and exhibits good high voltage cycle stability.
[0007] Preferably, the rare earth metal element Re accounts for 0.1-10% of the lithium atomic weight of the high-nickel positive electrode material with high voltage cycle stability; the rare earth metal element Re is doped into the lattice of the high-nickel matrix material to form a reinforced layered lattice structure.
[0008] Preferably, the thickness of the modified layer is 2 nm to 20 nm.
[0009] Preferably, the particle size of the high-nickel positive electrode material with high voltage and stable cycle stability is 5 μm to 15 μm.
[0010] Preferably, the high-voltage cycle-stable high-nickel positive electrode material has a charging cutoff voltage relative to Li / Li+ in the range of 4.2 to 5.0 V.
[0011] On the other hand, the present invention also provides a method for preparing a high-voltage cycle-stable high-nickel positive electrode material, wherein the high-voltage cycle-stable high-nickel positive electrode material comprises a high-nickel base material and a modified layer coated on the surface of the high-nickel base material; the structural formula of the modified layer is Li x AO y ; Wherein A is selected from one or more combinations of phosphorus, silicon, boron and aluminum, and 1≤x≤3, 1≤y≤5; The general structural formula of the high nickel matrix material is LiNi z Z 1-z O2, wherein Z is at least one of cobalt, manganese, iron, and aluminum, 0.5≤z<1, and the high-nickel matrix material is doped with a rare earth metal element Re, wherein Re is selected from at least one of lanthanum, cerium, praseodymium, samarium, scandium, and yttrium; the preparation method of the high-voltage cycle-stable high-nickel positive electrode material comprises:
[0012] (1) preparing transition metal hydroxides by a coprecipitation method;
[0013] (2) mixing a transition metal hydroxide with a solution containing an acid radical ion compound of the element A and a compound of the rare earth element Re, and subjecting the mixture to a hydrothermal treatment to obtain a modified hydroxide;
[0014] (3) The modified hydroxide is mixed with a lithium-containing compound and then calcined to obtain the high-voltage cycle-stable high-nickel positive electrode material.
[0015] In the present invention, the transition metal hydroxide precipitation solubility product is relatively close, a transition metal soluble salt solution is used as a raw material, ammonia water is used as a chelating agent, and a soluble hydroxide solution is added dropwise to generate a hydroxide precursor with uniform element distribution. Then, an aqueous solution containing an acid radical ion of the A element and a rare earth element Re compound is used, stirred and mixed with the precursor, and hydrothermally treated at a certain temperature to obtain a modified precursor. This method can ensure that the acid radical ions of the A element and the Re element are evenly distributed on the surface interface of the precursor, and then mixed evenly with the lithium-containing compound, and calcined in an oxygen atmosphere to obtain modified high-nickel positive electrode material secondary particles.
[0016] In the present invention, by introducing an acid radical ion compound containing element A into the precursor, a uniformly coated lithium-containing modified layer Li is generated in situ during the subsequent calcination and lithiation process. x AO y , which can effectively protect the high-nickel matrix material and slow down the electrolyte corrosion side reaction intensity during the cycle process, and the lithium compound coating layer, as a lithium ion conductor, has fast lithium ion transmission characteristics, and its uniform coating has a positive significance for improving the rate performance of high-nickel materials. In addition, by optimizing the amount of A element acid radical ion compound added, the excess lithium additive added in the calcination preparation stage can be fully consumed, and the problem of easy gelation of battery slurry caused by lithium residues on the surface of high-nickel materials is cleverly solved. Wherein A includes but is not limited to one or more combinations of phosphorus, silicon, boron and aluminum (preferably phosphorus), and 1≤x≤3, 1≤y≤5, the preferred compound containing A element acid radical ion compound is diammonium hydrogen phosphate, and further preferably, the molar ratio of transition metal hydroxide: phosphate ion compound is 1: (0.1-10%).
[0017] In the present invention, by introducing the rare earth element Re into the precursor, in the subsequent calcination and lithiation process, due to the diffusion of atoms, the rare earth element Re can migrate to the near-surface layered lattice structure of the high-nickel material to form a strong Re-O bond, thereby enhancing the lattice structure strength of the high-nickel material. By preferably doping the content of the rare earth element, the overall crystal phase of the material after calcination is still a layered structure with good crystallization performance. Wherein Re includes but is not limited to one or more combinations of lanthanum, cerium, praseodymium, samarium, scandium, and yttrium, preferably Re is lanthanum, and further preferably, the molar ratio of the transition metal hydroxide: rare earth element Re compound is 1: (0.1-10%).
[0018] In summary, the present invention introduces acid radical ions containing element A and rare earth element Re in the precursor stage, and the high-nickel positive electrode material obtained by high-temperature lithiation has a uniform and stable surface interface modification and a strongly bonded layered lattice structure. x AO yThe uniform coating and doping of rare earth elements realize the stable high voltage cycle of high nickel positive electrode material, which is an excellent new type of high nickel positive electrode material. In the present invention, the method is very simple.
[0019] Preferably, in step (1), the coprecipitation method is: coprecipitation reaction of transition metal salt solution and hydroxide solution at 30-90°C for 5-48 hours. Preferably, the coprecipitation temperature is 50°C and the reaction time is 24h. More preferably, the hydroxide precursor is Ni 0.8 Co 0.15 Mn 0.05 (OH)2.
[0020] Preferably, the solute in the transition metal salt solution is at least one of sulfates, nitrates and chlorides of transition metals nickel, manganese, cobalt and iron; the solute in the hydroxide solution is at least one of lithium hydroxide, sodium hydroxide and potassium hydroxide.
[0021] Preferably, in step (2), the temperature of the hydrothermal treatment is 80-250°C; the time of the hydrothermal treatment is 2-48 hours; preferably, the hydrothermal treatment is carried out under stirring. Preferably, the temperature of the hydrothermal reaction is 160°C and the reaction time is 8 hours. As an example, the transition metal hydroxide and the aqueous solution of two compounds containing lanthanum and phosphate are subjected to a stirring hydrothermal treatment at 80-250°C for 2-48 hours.
[0022] Preferably, in step (2), the molar ratio of the transition metal hydroxide: the A element acid radical ion compound: the rare earth element Re compound is 1:(0.1-10%):(0.1-10%), preferably 1:(0.1-5%):(0.1-5%).
[0023] Preferably, in step (3), the lithium-containing compound is at least one of lithium hydroxide, lithium carbonate, lithium acetate and lithium nitrate, preferably lithium hydroxide; preferably, the mass molar ratio of the modified hydroxide:lithium-containing compound is 1:(1.02-1.05).
[0024] Preferably, in step (3), the calcination includes two stages: the temperature of the first stage is to keep the temperature at 400-600°C for 3-10 hours; the temperature of the second stage is to raise the temperature to 700-850°C and keep the temperature for 5-25 hours; the calcination atmosphere is an oxygen atmosphere. Preferably, the temperature of the first stage is 500°C and kept for 3 hours; the temperature of the second stage is 780°C and kept for 5 hours. This is to calcine the positive electrode material in stages, the low temperature stage ensures the uniform mixing of the lithium salt (about 500°C is the melting point of the lithium salt), and the high temperature stage ensures the crystallinity. There is no need to compare this.
[0025] On the other hand, the present invention also provides an application of a high-voltage, cycle-stable high-nickel positive electrode material in a high-voltage positive electrode material for a lithium-ion battery.
[0026] Beneficial effects:
[0027] The method for preparing a high-nickel positive electrode material for a lithium-ion battery with high voltage cycle stability of the present invention comprises the following steps: uniformly distributing transition metal elements into a hydroxide precursor in the precursor preparation stage, uniformly mixing the hydroxide with aqueous solutions of two compounds containing acid radical ions of the element A and the rare earth element Re, and then subjecting the precursor to a hydrothermal treatment to obtain a modified precursor, which is then uniformly mixed with a lithium-containing compound, and calcined under an oxygen atmosphere to obtain a final product. Compared with traditional high-nickel positive electrode materials, this material has the advantages of a uniform coating layer and a more stable layered lattice structure. Even under high voltage and high lithium removal conditions, it still maintains good reversibility of lithium ion insertion and extraction reactions, thereby improving cycle stability under high voltage. The introduced acid radical ions containing the element A are subjected to a lithiumation and calcination treatment to obtain Li x AO y The cathode material is evenly coated in the form of a lithiation, which not only improves the interfacial stability of the material in the electrolyte, but also effectively promotes the transmission of lithium ions and improves the rate performance of the material. Through lithiation annealing treatment, the introduced rare earth element Re can migrate to the near-surface layered lattice structure of the high-nickel material to form a strongly bonded BO bond, thereby improving the layered structure stability of the material. This preparation method solves the problems of the difficulty in uniform distribution of transition metal elements, the relatively complex modification process and the poor high-voltage cycle stability in the existing preparation process. It can not only obtain a high-nickel cathode material with excellent performance under high voltage, but also simplify the modification process of the high-nickel cathode material, thereby reducing the synthesis cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 X-ray powder diffraction (XRD) of the precursor (Figure a) and the high-nickel positive electrode material (Figure b) prepared in Example 1 of the present invention;
[0029] Figure 2 A scanning electron microscope (SEM) of the high nickel cathode material prepared in Example 1 of the present invention;
[0030] Figure 3 The transmission electron microscope (TEM) of the high nickel positive electrode material prepared in Example 1 of the present invention clearly shows the coating and doping layers;
[0031] Figure 4 Element distribution diagram of the high-nickel positive electrode material prepared in Example 1 of the present invention (a is a SEM image, b is nickel element, c is cobalt element, c is manganese element, d is phosphorus element, and e is lanthanum element);
[0032] Figure 5The first-cycle electrochemical charge-discharge diagram of the high-nickel positive electrode material prepared in Example 1 of the present invention and Comparative Example 1 (B-LNCM represents the comparative example, LP-LNCM represents Example 1 of the present invention, the abscissa represents capacity, and the ordinate represents voltage);
[0033] Figure 6 The figure is a comparison chart of the cycle performance of the high nickel positive electrode material prepared in comparative example 1 and in embodiment 1 of the present invention (the abscissa is the cycle number, and the ordinate is the discharge capacity);
[0034] Figure 7 This is a SEM image of the high nickel positive electrode material prepared in Example 2 of the present invention;
[0035] Figure 8 XRD diagram of the high nickel positive electrode material prepared in Example 2 of the present invention;
[0036] Fig. 9 The first cycle electrochemical charge-discharge diagram of the high nickel positive electrode material prepared in Example 2 of the present invention (the abscissa is capacity and the ordinate is voltage);
[0037] Fig.10 This is a cycle performance diagram of the high nickel positive electrode material prepared in Comparative Example 2 of the present invention (the abscissa is the cycle number, and the ordinate is the discharge capacity);
[0038] Fig.11 The first-cycle electrochemical charge-discharge diagram of the high-nickel positive electrode material prepared in Comparative Example 3 of the present invention has capacity on the abscissa and voltage on the ordinate. DETAILED DESCRIPTION
[0039] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0040] In the present disclosure, the high-voltage cycle-stable high-nickel positive electrode material at least comprises: a high-nickel base material and a modified layer in situ coated on the surface. The modified layer is evenly distributed on the surface of the high-nickel base material, effectively protecting the high-nickel base material from erosion by side reactions during the cycle. The general structural formula is Li x AO y; Wherein A is selected from one or more combinations of phosphorus, silicon, boron and aluminum, and 1≤x≤3, 1≤y≤5. In addition, the high-nickel matrix material of the high-voltage cycle-stable high-nickel positive electrode material also has a reinforced layered structure constructed by doping the rare earth metal Re element in the near-surface high-nickel matrix material, which effectively avoids the collapse of the layered lattice structure and the generation of cracks in the high-nickel matrix material under the high-lithium desorption state caused by high voltage, and exhibits good high-voltage cycle stability. Wherein Re is selected from one or more combinations of lanthanum, cerium, praseodymium, samarium, scandium and yttrium, and the ionic radius of the above rare earth elements is easier to be incorporated into the Li position in the high-nickel matrix material.
[0041] In an optional embodiment, the high nickel matrix material may be any one or more transition metal oxides containing nickel, cobalt, manganese, iron, aluminum and the like, and the general formula is LiNi z Z 1-z O2, wherein Z is any two or more of the elements such as cobalt, manganese, iron, aluminum, etc., and 0.5≤z<1.
[0042] Therefore, the high-nickel cathode material with high voltage cycle stability has a uniform coating layer and a reinforced layered lattice structure, which can effectively inhibit the particle surface reconstruction side reaction and layered structure destruction of the material under high voltage cycle, and improve the high voltage cycle stability. High voltage is the electrochemical performance test of lithium-ion batteries relative to Li / Li + The charging cut-off voltage is in the range of 4.2-5.0V.
[0043] The preparation method of the high-nickel positive electrode material for lithium-ion batteries with high voltage cycle stability of the present invention comprises the following steps: preparing a transition metal hydroxide precursor by a coprecipitation method, uniformly mixing the precursor with two aqueous solutions of compounds containing rare earth elements and phosphate, hydrothermally treating to obtain a modified precursor, directly mixing the modified precursor with a lithium-containing compound, and then calcining under an oxygen atmosphere to obtain a high-nickel positive electrode material for lithium-ion batteries with high voltage cycle stability. The following is an exemplary description of the preparation method of the high-nickel positive electrode material provided by the present invention.
[0044] The transition metal salt solution and the soluble hydroxide solution are subjected to a coprecipitation reaction at a certain temperature, and the obtained transition metal hydroxide precipitate is washed with deionized water, and then dried to obtain a precursor. The precursor powder is evenly mixed with an aqueous solution of two compounds containing an acid radical ion of the element A and a rare earth element Re, and then hydrothermally reacted for a period of time to obtain a modified hydroxide precursor. The modified precursor is evenly mixed with an appropriate amount of a lithium-containing compound, and calcined under an oxygen atmosphere to obtain a high-nickel positive electrode material with high voltage cycle stability. In the present invention, the transition metal salt solution is a mixed solution of one or more of sulfates, nitrates, and chlorides of transition metals such as nickel, cobalt, manganese, and iron; the hydroxide is a mixed solution of one or more of lithium hydroxide, sodium hydroxide, and potassium hydroxide. The obtained precursor is preferably Ni 0.8 Co 0.15 Mn 0.05 (OH)2. The A element includes but is not limited to one or more combinations of phosphorus, silicon, boron and aluminum, preferably phosphorus; the Re element includes but is not limited to one or a mixture of two or more of lanthanum, cerium, praseodymium, samarium, scandium and yttrium, preferably lanthanum; the lithium-containing compound is one or a mixture of two or more of lithium hydroxide, lithium carbonate, lithium acetate and lithium nitrate, preferably lithium hydroxide. The obtained high-voltage cycle-stable high-nickel positive electrode material has a uniform coating layer, and the acid radical ion compound of the A element is uniformly introduced on the surface of the precursor to generate Li in situ with the lithium-containing compound. x AO y Uniform coating on the surface of high-nickel cathode materials can effectively stabilize the material surface interface and inhibit the deactivation side reaction with the electrolyte during the cycle. The obtained high-voltage cycle-stable high-nickel cathode material has a reinforced layered lattice structure. By introducing the rare earth element Re, along with the atomic diffusion process in the calcination preparation stage, the rare earth element Re migrates into the near-surface layered structure to form strong bonds with oxygen atoms, thereby improving the stability of the layered structure and avoiding the collapse of the layered lattice structure and the generation of cracks under the high delithiation state caused by high voltage.
[0045] The transition metal hydroxide precursor is prepared by coprecipitation reaction. As an example, a transition metal salt solution and a hydroxide solution are precipitated at 30-90°C. Ammonia water is added dropwise as a complexing agent during the reaction. Nitrogen is continuously introduced to promote dispersion. The reaction time lasts for 5-48 hours. The obtained transition metal hydroxide precipitate is washed and dried to obtain the precursor powder. The preferred temperature is 50°C and the reaction time is 24 hours.
[0046] The precursor powder is uniformly mixed with aqueous solutions of two compounds containing acid radical ions of element A and rare earth element Re, and then subjected to hydrothermal reaction for a period of time to obtain a modified hydroxide precursor. As an example, the precursor powder is uniformly mixed with aqueous solutions of two compounds containing lanthanum and phosphate, and then subjected to hydrothermal treatment at 80-250°C with stirring for 2-48h. The obtained precipitate is washed and dried to obtain the modified precursor. The preferred reaction temperature is 160°C and the reaction time is 8h;
[0047] The modified precursor is evenly mixed with an appropriate amount of lithium-containing compound, and calcined in an oxygen atmosphere to obtain a high-nickel positive electrode material with high voltage cycle stability. As an example, the modified precursor is evenly mixed with the lithium-containing compound. The temperature in the first stage is 400-600°C for 3-10 hours. Its function is to evenly mix the lithium-containing compound with the precursor; the temperature in the second stage is 700-850°C for 5-25 hours to ensure good crystallinity of the product. The calcination atmosphere is oxygen. Preferably: the temperature in the first stage is 500°C, kept warm for 3 hours, and the temperature in the second stage is 780°C, kept warm for 5 hours.
[0048] As a detailed example of the preparation of a high nickel cathode material for lithium-ion batteries with high voltage cycling stability, the preparation process is as follows:
[0049] (1) A soluble transition metal salt is dispersed in deionized water, and then a soluble hydroxide solution is added dropwise, and an ammonia solution is added while continuously stirring, and nitrogen gas is continuously introduced to promote dispersion. A precipitate is generated by the reaction, and the precipitate is washed several times with deionized water and dried to obtain a precursor powder.
[0050] (2) The precursor powder is uniformly mixed with aqueous solutions of two compounds containing acid radical ions of element A and rare earth element Re, stirred and hydrothermally treated, and the precipitate is washed several times and dried to obtain a modified precursor.
[0051] (3) The modified precursor is uniformly mixed with the lithium-containing compound and calcined in an oxygen atmosphere to obtain the final product.
[0052] The present invention prepares the transition metal hydroxide precursor by coprecipitation, and then modifies the precursor by rare earth elements and acid radical ions containing element A, and finally mixes lithium and calcines to obtain a high-nickel positive electrode material for lithium-ion batteries with high voltage and stable cycle. The main advantages are as follows: First, the modified high-nickel positive electrode material can be synthesized in one step by adopting the precursor modification method, avoiding the secondary calcination process of direct modification of the high-nickel positive electrode material, saving energy. Second, the Li x AO y The strategy effectively removed the residual lithium on the surface of the high-nickel material, and the generated Li x AO yEvenly distributed on high-nickel materials, it not only promotes lithium ion transmission, but also effectively protects the material from electrolyte corrosion. Third, by introducing rare earth elements, the layered lattice structure near the surface of high-nickel materials is stabilized, which inhibits the collapse of the layered structure and the generation of cracks in the high-lithium depletion state caused by high voltage, and improves the high-voltage cycle stability of the material.
[0053] The high nickel cathode material obtained by the present invention has excellent electrochemical performance, and the first cycle capacity reaches 220 mAh g -1 Above (test conditions: 2.8-4.8V, 0.1C, 25℃), after 100 cycles, the capacity retention rate reaches more than 80%.
[0054] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0055] Example 1
[0056] 2 mol / L NSO4 (N=Ni, Co, Mn, where the molar ratio of Ni:Co:Mn is 0.8:0.15:0.05) solution and 4 mol / L NaOH solution were added dropwise to the reaction vessel at a rate of 1 mL / min. Ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction, the reaction was washed and dried. The dried 2 g N(OH)2 was mixed with 5 ml La(NO3)3 (0.01 mol / L) and 5 ml (NH4)2HPO4 (0.01 mol / L) solution were uniformly mixed in deionized water, then poured into a reactor and stirred at 160°C for 8 h. The product was washed and dried and uniformly mixed with LiOH·H2O (molar ratio Li:N=1.03:1), placed in a tube furnace, heated to 500°C in an oxygen atmosphere and kept warm for 3 hours, then heated to 780°C and kept warm for 5 hours to obtain modified high-nickel cathode material secondary particles with good crystallinity, whose structural formula is Li3PO4@Li 0.9888 La 0.0112 Ni 0.8 Co 0.15 Mn 0.05O2. This material was assembled into a CR2032 button cell to test the electrochemical performance. Specifically: according to the active material: PVDF: acetylene black = 8:1:1 (mass ratio), the mixture was weighed and then smeared, then vacuum dried at 90°C, cut into pole pieces with a diameter of about 12mm, and assembled in an argon glove box (water and oxygen content ≤ 0.5ppm). The assembled battery was left to stand for 12 hours before various electrochemical performance tests were performed.
[0057] Figure 1 is the powder diffraction pattern of the precursor and high nickel positive electrode material prepared in Example 1, such as Figure 1 As shown in a, the characteristic peaks of the obtained precursor are similar to those of Ni(OH)2, showing a hexagonal P-3m1(164) structure. After lithiation and calcination, it can be clearly seen that ( Figure 1 In b), the prepared modified high-nickel positive electrode material exhibits typical layered structural characteristics. Figure 2 a in the figure is the microscopic morphology of the high nickel material prepared in Example 1, and its primary particles are in the form of flakes. Figure 2 Middle b is a low-magnification image, and the morphology is spherical secondary particles formed by the accumulation of primary particles. Figure 3 This is a transmission electron microscope image of the high-nickel positive electrode material prepared in Example 1. It can be seen that the bulk phase of the prepared high-nickel positive electrode material shows a layered structure with clear lattice fringes and a coating layer at the boundary. Due to La doping, a phase change occurs in the near-surface structure. Figure 4 This is the distribution diagram of each element of the high nickel cathode material prepared in Example 1. It can be seen from the figure that the elements of the prepared high nickel cathode material are evenly distributed, indicating that lanthanum and phosphorus can be evenly distributed on the particles through hydrothermal treatment. The button cell was assembled to test the electrochemical performance. When the test voltage was between 2.8-4.8V, the obtained first discharge capacity reached 226mAh g -1 ( Figure 5 ). The capacity retention rate after 100 cycles at 0.2C current is 88% ( Figure 6 ), it can be seen from the electrochemical performance test that the high nickel positive electrode material prepared in Example 1 has no significant change in the first cycle capacity compared with the control example, but its rate performance and high voltage cycle capacity retention rate are significantly improved, which proves the effectiveness of the modification strategy.
[0058] Example 2
[0059] 2 mol / L NSO4 (N=Ni, Co, Mn, where the molar ratio of Ni:Co:Mn is 0.8:0.15:0.05) solution and 4 mol / L NaOH solution were added dropwise to the reaction vessel at a rate of 1 mL / min. Ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction, the reaction was washed and dried. The dried 2 g N(OH)2 was mixed with 5 ml La(NO3)3 (0.01 mol / L) and 5 ml (NH4)2HPO4 (0.01 mol / L) solution were uniformly mixed in deionized water, then poured into a reactor and stirred for reaction at 160°C for 8 hours. The product was washed and dried and uniformly mixed with Li2CO3 (molar ratio Li:N=1.03:1), placed in a tube furnace, heated to 500°C in an oxygen atmosphere and kept warm for 3 hours, then heated to 780°C and kept warm for 5 hours to obtain a modified high-nickel positive electrode material with good crystallinity, whose structural formula is Li3PO4@Li 0.9888 La 0.0112 Ni 0.8 Co 0.15 Mn 0.05 O2. This material was assembled into a CR2032 button cell to test the electrochemical performance. Specifically: according to the active material: PVDF: acetylene black = 8:1:1 (mass ratio), the mixture was weighed and then smeared, then vacuum dried at 90°C, cut into pole pieces with a diameter of about 12mm, and assembled in an argon glove box (water and oxygen content ≤ 0.5ppm). The assembled battery was left to stand for 12 hours before various electrochemical performance tests were performed. Figure 7 This is a scanned image of the high nickel cathode material prepared in Example 2, which is a spherical secondary particle formed by the accumulation of thick flake primary particles. XRD powder diffraction data ( Figure 8 ) shows that the material prepared in Example 2 has good crystallinity and a typical layered structure. When the test voltage is between 2.8-4.8V, the first discharge capacity reaches 214mAh g -1 ( Fig. 9 ), after 100 cycles of charge and discharge, the capacity retention rate reached more than 80%.
[0060] Example 3
[0061] 2 mol / L NCl2 (N=Ni, Co, Mn, where the molar ratio of Ni:Co:Mn is 0.8:0.15:0.05) solution and 4 mol / L NaOH solution were added dropwise to the reaction vessel at a rate of 1 mL / min. Ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction, the reaction was washed and dried. The dried 2 g N(OH)2 was mixed with 5 ml La(NO3)3 (0.01 mol / L) and 5 ml (NH4)2HPO4 (0.01 mol / L) solution were uniformly mixed in deionized water, and then placed in a reactor to react at 160°C for 8 hours. The product was washed and dried and uniformly mixed with Li2CO3 (molar ratio Li: N = 1.03:1), and then placed in a tube furnace. In an oxygen atmosphere, the temperature was raised to 500°C and kept for 3 hours, and then raised to 780°C and kept for 5 hours to obtain a high-nickel positive electrode material with good crystallinity, whose structural formula is Li3PO4@Li 0.9888 La 0.0112 Ni 0.8 Co 0.15 Mn 0.05 O2. This material was assembled into a CR2032 button cell to test the electrochemical performance. Specifically: according to the active material: PVDF: acetylene black = 8:1:1 (mass ratio), the mixture was weighed and then smeared, then vacuum dried at 90°C, cut into pole pieces with a diameter of about 12mm, and assembled in an argon glove box (water and oxygen content ≤ 0.5ppm). The assembled battery was left to stand for 12 hours before various electrochemical performance tests were performed. When the test voltage was between 2.8-4.8V, the first discharge capacity reached 218mAh g -1 After 100 cycles of charge and discharge, the capacity retention rate reaches more than 80%.
[0062] Example 4
[0063] 2 mol / L N(NO3)2 (N=Ni, Co, Mn, where the molar ratio of Ni:Co:Mn is 0.8:0.15:0.05) solution and 4 mol / L NaOH solution were added dropwise to the reaction vessel at a rate of 1 mL / min. Ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction, the reaction was washed and dried. The dried 2 g N(OH)2 was mixed with 5 ml La(NO3)3 (0.01 mol / L) and 5 ml (NH4)2HPO4 (0.01 mol / L) solution were uniformly mixed in deionized water, and then placed in a reactor to react at 160°C for 8 hours. The product was washed and dried and uniformly mixed with Li2CO3 (molar ratio Li: N = 1.03:1), and then placed in a tube furnace. In an oxygen atmosphere, the temperature was raised to 500°C and kept for 3 hours, and then raised to 780°C and kept for 5 hours to obtain a high-nickel positive electrode material with good crystallinity, whose structural formula is Li3PO4@Li 0.9888 La 0.0112 Ni 0.8 Co 0.15 Mn 0.05 O2. This material was assembled into a CR2032 button cell to test the electrochemical performance. Specifically: according to the active material: PVDF: acetylene black = 8:1:1 (mass ratio), the mixture was weighed and then smeared, then vacuum dried at 90°C, cut into pole pieces with a diameter of about 12mm, and assembled in an argon glove box (water and oxygen content ≤ 0.5ppm). The assembled battery was left to stand for 12 hours before various electrochemical performance tests were performed. When the test voltage was between 2.8-4.8V, the first discharge capacity reached 219mAh g -1 After 100 cycles of charge and discharge, the capacity retention rate reaches more than 80%.
[0064] Example 5
[0065] 2 mol / L N(NO3)2 (N=Ni, Co, Mn, where the molar ratio of Ni:Co:Mn is 0.8:0.15:0.05) solution and 4 mol / L KOH solution were added dropwise to the reaction vessel at a rate of 1 mL / min. Ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction, the reaction was washed and dried. The dried 2g N(OH)2 was mixed with 5ml La(NO3)3 (0.01 mol / L) and 5 ml (NH4)2HPO4 (0.01 mol / L) solution were uniformly mixed in deionized water, and then placed in a reactor to react at 160°C for 8 hours. The product was washed and dried and uniformly mixed with Li2CO3 (molar ratio Li: N = 1.03:1), and then placed in a tube furnace. In an oxygen atmosphere, the temperature was raised to 500°C and kept for 3 hours, and then raised to 780°C and kept for 5 hours to obtain a high-nickel positive electrode material with good crystallinity, whose structural formula is Li3PO4@Li 0.9888 La 0.0112 Ni 0.8 Co 0.15 Mn 0.05 O2. This material was assembled into a CR2032 button cell to test the electrochemical performance. Specifically: according to the active material: PVDF: acetylene black = 8:1:1 (mass ratio), the mixture was weighed and then smeared, then vacuum dried at 90°C, cut into pole pieces with a diameter of about 12mm, and assembled in an argon glove box (water and oxygen content ≤ 0.5ppm). The assembled battery was left to stand for 12 hours before various electrochemical performance tests were performed. When the test voltage was between 2.8-4.8V, the first discharge capacity reached 223mAh g -1 After 100 cycles of charge and discharge, the capacity retention rate reaches more than 80%.
[0066] Example 6
[0067] 2 mol / L N(NO3)2 (N=Ni, Co, Mn, where the molar ratio of Ni:Co:Mn is 0.8:0.15:0.05) solution and 4 mol / L KOH solution were added dropwise to the reaction vessel at a rate of 1 mL / min. Ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction, the reaction was washed and dried. The dried 2g N(OH)2 was mixed with 8ml Ce(NO3)3 (0.01 mol / L) and 8 ml (NH4)2HPO4 (0.01 mol / L) solution were uniformly mixed in deionized water, and then placed in a reactor to react at 160°C for 8 hours. The product was washed and dried and uniformly mixed with Li2CO3 (molar ratio Li: N = 1.03:1), and then placed in a tube furnace. In an oxygen atmosphere, the temperature was raised to 500°C and kept warm for 3 hours, and then raised to 780°C and kept warm for 5 hours to obtain secondary particles of high nickel positive electrode material with good crystallinity, whose structural formula is Li3PO4@Li 0.982 Ce 0.018 Ni 0.8 Co 0.15 Mn 0.05 O2.
[0068] Example 7
[0069] 2 mol / L N(NO3)2 (N=Ni, Co, Mn, where the molar ratio of Ni:Co:Mn is 0.8:0.15:0.05) solution and 4 mol / L KOH solution were added dropwise to the reaction vessel at a rate of 1 mL / min. Ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction, the reaction was washed and dried. The dried 2g N(OH)2 was mixed with an appropriate amount of 12ml Y(NO3)3 (0.01 mol / L) and 12 ml (NH4)2HPO4 (0.01 mol / L) solution were uniformly mixed in deionized water, and then placed in a reactor to react at 160°C for 8 hours. The product was washed and dried and uniformly mixed with Li2CO3 (molar ratio Li: N = 1.03:1), and then placed in a tube furnace. In an oxygen atmosphere, the temperature was raised to 500°C and kept warm for 3 hours, and then raised to 780°C and kept warm for 5 hours to obtain secondary particles of high nickel positive electrode material with good crystallinity, whose structural formula is Li3PO4@Li 0.973 Y 0.027 Ni 0.8 Co 0.15 Mn 0.05 O2.
[0070] Example 8
[0071] 2 mol / L N(NO3)2 ((N=Ni, Co, Mn, where the molar ratio of Ni:Co:Mn is 0.8:0.15:0.05) solution and 4 mol / L KOH solution were added dropwise to the reaction vessel at a rate of 1 mL / min. Ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction, it was washed and dried. The dried 2g N(OH)2 was mixed with an appropriate amount of 5ml Sm(NO3)3 (0.01 mol / L) and 5 ml (NH4)2HPO4 (0.01 mol / L) solution were uniformly mixed in deionized water, and then placed in a reactor to react at 160°C for 8 hours. The product was washed and dried and uniformly mixed with Li2CO3 (molar ratio Li: N = 1.03:1), and then placed in a tube furnace. In an oxygen atmosphere, the temperature was raised to 500°C and kept warm for 3 hours, and then raised to 780°C and kept warm for 5 hours to obtain secondary particles of high nickel positive electrode material with good crystallinity, whose structural formula is Li3PO4@Li 0.988 Sm 0.0112 Ni 0.8 Co 0.15 Mn 0.05 O2.
[0072] Example 9
[0073] 2 mol / L N(NO3)2 ((N=Ni, Co, Mn, wherein the molar ratio of Ni:Co:Mn is 0.8:0.15:0.05) solution and 4 mol / L KOH solution were added dropwise into the reaction vessel at a rate of 1 mL / min, and ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction, the mixture was washed and dried. The dried 2g N(OH)2 was mixed with an appropriate amount of 5ml La(NO3)3 (0.01mol / L), 5ml The H3PO4 (0.01 mol / L) solution was uniformly mixed in deionized water, and then placed in a reactor to react at 160°C for 8 hours. The product was washed and dried, and then uniformly mixed with Li2CO3 (molar ratio Li:N=1.03:1), and then placed in a tube furnace. In an oxygen atmosphere, the temperature was raised to 500°C and kept for 3 hours, and then raised to 780°C and kept for 5 hours to obtain secondary particles of high-nickel positive electrode material with good crystallinity, whose structural formula is Li3PO4@Li 0.9888 La 0.0112 Ni 0.8 Co 0.15 Mn 0.05 O2.
[0074] Example 10
[0075] 2 mol / L NSO4 ((N=Ni, Co, Mn, where the molar ratio of Ni:Co:Mn is 0.8:0.1:0.1) solution and 4 mol / L KOH solution were added dropwise to the reaction vessel at a rate of 1 mL / min, and ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction was completed, washing and drying were performed. The dried 2g N(OH)2 was mixed with an appropriate amount of 5ml La(NO3)3 (0.01 mol / L) and 5 ml (NH4)2HPO4 (0.01 mol / L) solution were uniformly mixed in deionized water, and then placed in a reactor to react at 160°C for 8 hours. The product was washed and dried and uniformly mixed with Li2CO3 (molar ratio Li: N = 1.03:1), and then placed in a tube furnace. In an oxygen atmosphere, the temperature was raised to 500°C and kept warm for 3 hours, and then raised to 780°C and kept warm for 5 hours to obtain secondary particles of high nickel positive electrode material with good crystallinity, whose structural formula is Li3PO4@Li 0.9888 La 0.0112 Ni 0.8 Co 0.1 Mn 0.1 O2.
[0076] Embodiment 11
[0077] 2 mol / L NSO4 ((N=Ni, Co, Mn, where the molar ratio of Ni:Co:Mn is 0.6:0.2:0.2) solution and 4 mol / L KOH solution were added dropwise to the reaction vessel at a rate of 1 mL / min, and ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction was completed, washing and drying were performed. The dried 2g N(OH)2 was mixed with an appropriate amount of 5ml La(NO3)3 (0.01 mol / L) and 5 ml (NH4)2HPO4 (0.01 mol / L) solution were uniformly mixed in deionized water, and then placed in a reactor to react at 160°C for 8 hours. The product was washed and dried and uniformly mixed with Li2CO3 (molar ratio Li: N = 1.03:1), and then placed in a tube furnace. In an oxygen atmosphere, the temperature was raised to 500°C and kept warm for 3 hours, and then raised to 780°C and kept warm for 5 hours to obtain secondary particles of high nickel positive electrode material with good crystallinity, whose structural formula is Li3PO4@Li 0.9888 La 0.0112 Ni 0.6 Co 0.2 Mn 0.2 O2.
[0078] Example 12
[0079] 2 mol / L NSO4 ((N=Ni, Co, Mn, where the molar ratio of Ni:Co:Mn is 0.5:0.3:0.2) solution and 4 mol / L KOH solution were added dropwise to the reaction vessel at a rate of 1 mL / min. Ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction was completed, washing and drying were performed. The dried 2 g N(OH)2 was mixed with an appropriate amount of 5 ml La(NO3)3 (0.01 mol / L) and 5 ml (NH4)2HPO4 (0.01 mol / L) solution were uniformly mixed in deionized water, and then placed in a reactor to react at 160°C for 8 hours. The product was washed and dried and uniformly mixed with Li2CO3 (molar ratio Li: N = 1.03:1), and then placed in a tube furnace. In an oxygen atmosphere, the temperature was raised to 500°C and kept warm for 3 hours, and then raised to 780°C and kept warm for 5 hours to obtain secondary particles of high nickel positive electrode material with good crystallinity, whose structural formula is Li3PO4@Li 0.9888 La 0.0112 Ni 0.5 Co 0.3 Mn 0.2 O2.
[0080] Embodiment 13
[0081] 2 mol / L NSO4 (N=Ni, Co, Mn, wherein the molar ratio of Ni:Co:Mn is 0.8:0.15:0.05) solution and 4 mol / L NaOH solution were added dropwise into the reaction vessel at a rate of 1 mL / min, and ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction, the mixture was washed and dried. The dried 2 g N(OH)2 was mixed with an appropriate amount of 5 ml La(NO3)3 (0.01 mol / L), 5 ml Al(NO3)3 (0.01 mol / L) solution was uniformly mixed in deionized water, then poured into a reactor and stirred at 160°C for 8 hours. The product was washed and dried, then uniformly mixed with LiOH·H2O (molar ratio Li:N=1.03:1), placed in a tube furnace, heated to 500°C in an oxygen atmosphere, and then kept warm for 3 hours, and then heated to 780°C and kept warm for 5 hours to obtain a modified high-nickel cathode material secondary particle with good crystallinity, whose structural formula is LiAlO2@Li 0.9888 La 0.0112 Ni 0.8 Co 0.15 Mn 0.05 O2.
[0082] Embodiment 14
[0083] 2 mol / L NSO4 (N=Ni, Co, Mn, wherein the molar ratio of Ni:Co:Mn is 0.8:0.15:0.05) solution and 4 mol / L NaOH solution were added dropwise into the reaction vessel at a rate of 1 mL / min, and ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction, the mixture was washed and dried. The dried 2 g N(OH)2 was mixed with an appropriate amount of 5 ml La(NO3)3 (0.01 mol / L), 5 ml Li2SiO3 (0.01 mol / L) solution was uniformly mixed in deionized water, then poured into a reactor and stirred at 160°C for 8 hours. The product was washed and dried, uniformly mixed with LiOH·H2O (molar ratio Li:N=1.03:1), placed in a tube furnace, heated to 500°C in an oxygen atmosphere and kept warm for 3 hours, then heated to 780°C and kept warm for 5 hours, to obtain modified high-nickel cathode material secondary particles with good crystallinity, whose structural formula is Li2SiO3@Li 0.9888 La 0.0112 Ni 0.8 Co 0.15 Mn 0.05 O2.
[0084] Embodiment 15
[0085] 2 mol / L NSO4 (N=Ni, Co, Mn, wherein the molar ratio of Ni:Co:Mn is 0.8:0.15:0.05) solution and 4 mol / L NaOH solution were added dropwise into the reaction vessel at a rate of 1 mL / min, and ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction, the mixture was washed and dried. The dried 2 g N(OH)2 was mixed with an appropriate amount of 5 ml La(NO3)3 (0.01 mol / L), 5 ml Li3BO3 (0.01 mol / L) solution was uniformly mixed in deionized water, then poured into a reactor and stirred at 160°C for 8 hours. The product was washed and dried, and then uniformly mixed with LiOH·H2O (molar ratio Li:N=1.03:1), placed in a tube furnace, heated to 500°C in an oxygen atmosphere, and then kept warm for 3 hours, and then heated to 780°C and kept warm for 5 hours to obtain a modified high-nickel cathode material secondary particle with good crystallinity, whose structural formula is Li3BO3@Li 0.9888 La 0.0112 Ni 0.8 Co 0.15 Mn 0.05 O2.
[0086] Comparative Example 1
[0087] 2 mol / L NSO4 (N=Mn, Ni, Co, wherein the molar ratio of Mn:Ni:Co is 0.8:0.15:0.05) solution and 4 mol / L NaOH solution are added dropwise to the reaction container at a rate of 1 mL / min, and ammonia water is added to keep the pH value stable, and nitrogen is continuously introduced to promote dispersion, and the coprecipitation reaction is controlled to be 50°C. After the reaction is completed, washing and drying are performed, and the dried N(OH)2 is evenly mixed with LiOH·H2O (molar ratio Li:precursor=1.03:1), and then placed in a tubular furnace, heated to 500°C in an oxygen atmosphere, and then kept warm for 3 hours, and then heated to 780°C and kept warm for 5 hours, so as to obtain secondary particles of high nickel positive electrode material, whose structural formula is LiNi 0.8 Co 0.15 Mn 0.05 O2. Specifically: according to the active material: PVDF: acetylene black = 8:1:1 (mass ratio), weigh and mix the materials and apply them on the sheet, then vacuum dry them at 90℃, cut them into pole pieces with a diameter of about 12mm, and assemble the battery in an argon glove box (water and oxygen content ≤ 0.5ppm). After the assembled battery is left to stand for 12 hours, various electrochemical performance tests are performed. Figure 5 It can be seen that when the test voltage is between 2.8-4.8V, the first discharge capacity of the comparative material is 230mAhg -1 , compared with the high nickel cathode material prepared in Example 1, the rate performance is poor ( Figure 6 ), the capacity retention rate after 100 cycles at 0.2C current is only 45.32% ( Figure 7 ).
[0088] Comparative Example 2
[0089] 2 mol / L NSO4 (N=Ni, Co, Mn, where the molar ratio of Ni:Co:Mn is 0.8:0.15:0.05) solution and 4 mol / L NaOH solution were added dropwise to the reaction vessel at a rate of 1 mL / min, and ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion. The coprecipitation reaction was controlled at 50°C. After the reaction was completed, it was washed and dried. The dried 2 g N(OH)2 and an appropriate amount of 5ml (NH4)2HPO4 (0.01mol / L) solution were uniformly mixed in deionized water, then poured into a reactor and stirred for reaction at 160°C for 8h. The product was washed and dried and uniformly mixed with LiOH·H2O (molar ratio Li:N=1.03:1), placed in a tube furnace, heated to 500°C in an oxygen atmosphere and kept warm for 3 hours, then heated to 780°C and kept warm for 5 hours to obtain modified high-nickel cathode material secondary particles with good crystallinity, whose structural formula is Li3PO4@LiNi 0.8 Co 0.15 Mn 0.05O2. This material was used to assemble a CR2032 button cell and test its electrochemical performance. Specifically, the active material: PVDF: acetylene black = 8:1:1 (mass ratio) was weighed and mixed, and then dried in a vacuum oven at 90°C, cut into electrodes with a diameter of about 12 mm, and assembled in an argon glove box (water and oxygen content ≤ 0.5 ppm). The assembled battery was left to stand for 12 hours before various electrochemical performance tests were performed. Fig.10 It can be seen that when the test voltage is between 2.8-4.8V, the capacity retention rate after 100 cycles at 0.2C current is only 65.58%.
[0090] Comparative Example 3
[0091] 2 mol / L NSO4 (N=Ni, Co, Mn, wherein the molar ratio of Ni:Co:Mn is 0.8:0.15:0.05) solution and 4 mol / L NaOH solution were added dropwise to the reaction vessel at a rate of 1 mL / min, and ammonia water was added to keep the pH value stable. Nitrogen was continuously introduced to promote dispersion, and the coprecipitation reaction was controlled at 50°C. After the reaction, washing and drying were carried out. The dried 2g N(OH)2 and 50ml La(NO3)3 (0.1 mol / L) solution were uniformly mixed in deionized water, and then poured into a reactor and stirred at 160°C for 8 hours. The product was washed and dried and uniformly mixed with LiOH·H2O (molar ratio Li:N=1.03:1), placed in a tubular furnace, heated to 500°C in an oxygen atmosphere, and then heated to 780°C and kept warm for 5 hours to obtain secondary particles of high nickel positive electrode material. This material was used to assemble a CR2032 button cell and test its electrochemical performance. Specifically, the active material: PVDF: acetylene black = 8:1:1 (mass ratio) was weighed and mixed, and then dried in a vacuum oven at 90°C, cut into electrodes with a diameter of about 12 mm, and assembled in an argon glove box (water and oxygen content ≤ 0.5 ppm). The assembled battery was left to stand for 12 hours before various electrochemical performance tests were performed. Fig.11 It can be seen that when the test voltage is between 2.8-4.8V, the capacity is only 157mAh g at 0.2C current. -1 .
[0092] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a high-nickel positive electrode material with high voltage cycle stability, characterized in that: The high-voltage cycle-stable high-nickel positive electrode material comprises a high-nickel base material and a modified layer coated on the surface of the high-nickel base material; the structural formula of the modified layer is Li x AO y ; Wherein A is selected from one or more combinations of phosphorus, silicon, boron and aluminum, and 1≤x≤3, 1≤y≤5; The general structural formula of the high nickel matrix material is LiNi z Z 1-z O2, wherein Z is at least one of cobalt, manganese, iron, and aluminum, 0.5≤z<1, and the high-nickel matrix material is doped with a rare earth metal element Re, wherein Re is selected from at least one of lanthanum, cerium, praseodymium, samarium, scandium, and yttrium; the rare earth metal element Re is doped into the lattice of the high-nickel matrix material to form a reinforced layered lattice structure; The method for preparing the high-voltage cycle-stable high-nickel positive electrode material comprises: (1) Preparing transition metal hydroxides by coprecipitation method; (2) mixing a transition metal hydroxide with a solution containing an acid radical ion compound of element A and a compound of a rare earth element Re, and subjecting the mixture to a hydrothermal treatment to obtain a modified hydroxide; The molar ratio of the transition metal hydroxide: the A element acid radical ion compound: the rare earth element Re compound is 1: (0.1-10%): (0.1-10%); (3) mixing the modified hydroxide with the lithium-containing compound and calcining the mixture to obtain the high-voltage cycle-stable high-nickel positive electrode material; The calcination comprises two stages: the first stage is to keep the temperature at 400-600°C for 3-10 hours; the second stage is to raise the temperature to 700-850°C and keep the temperature for 5-25 hours.
2. The preparation method according to claim 1, characterized in that: The rare earth metal element Re accounts for 0.1 to 10% of the lithium atomic weight of the high-nickel positive electrode material with high voltage cycle stability.
3. The preparation method according to claim 1, characterized in that: The thickness of the modified layer is 2nm to 20nm.
4. The preparation method according to claim 1, characterized in that: The particle size of the high-nickel positive electrode material with high voltage and stable cycle is 5 μm to 15 μm.
5. The preparation method according to claim 1, characterized in that The high-voltage cycle-stable high-nickel positive electrode material has a charging cutoff voltage in the range of 4.2 to 5.0 V relative to Li / Li+.
6. The preparation method according to claim 1, characterized in that: In step (1), the coprecipitation method is: a transition metal salt solution and a hydroxide solution are subjected to a coprecipitation reaction at 30 to 90° C. for 5 to 48 hours.
7. The preparation method according to claim 6, characterized in that: The solute in the transition metal salt solution is at least one of sulfates, nitrates and chlorides of transition metals nickel, manganese, cobalt and iron; the solute in the hydroxide solution is at least one of lithium hydroxide, sodium hydroxide and potassium hydroxide.
8. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the hydrothermal treatment is 80 to 250° C.; and the time of the hydrothermal treatment is 2 to 48 hours.
9. The preparation method according to claim 1, characterized in that: In step (3), the lithium-containing compound is at least one of lithium hydroxide, lithium carbonate, lithium acetate, and lithium nitrate; and the molar ratio of the modified hydroxide:lithium-containing compound is 1:(1.02-1.05).
10. The preparation method according to claim 1, characterized in that: In step (3), the calcination atmosphere is an oxygen atmosphere.
11. Use of the high-voltage, cycle-stable high-nickel positive electrode material obtained by the preparation method according to claim 1 in high-voltage positive electrode materials for lithium-ion batteries.
